Pan-cancer analysis of phagocytosis regulators in female-specific cancers: a focus on HMGB2 - Lu, Xiaoqin; Ren, Dan; Zhao, Panpan; Li, Yanfang; Wang, Zhenhui; Zhang, Jingyan (Frontiers in Immunology, 2025)
IntroductionTumor-associated macrophages (TAMs) play a crucial role in the tumor microenvironment, regulating immune escape and promoting cancer progression. Understanding the role of phagocytosis regulators in female-specific cancers is essential for developing effective therapeutic strategies.MethodsWe performed comprehensive analyses of public databases to evaluate the expression, somatic mutations, and copy number variations of phagocytosis regulators. DNA methylation patterns, biological pathways, survival outcomes, and drug sensitivity were assessed. Additionally, immune modulators, immune cell infiltration, and single-cell sequencing were used to explore alterations in phagocytosis and their cellular origins. The functional role of HMGB2 in tumor cell behavior was validated through in vitro assays.ResultsPhagocytosis regulators exhibited differential expression across various female-specific cancers, with key genes such as CD47 and FOXO1 playing significant roles in modulating tumor progression. High-frequency mutations were found in PTEN, ARID1A, and UBR4. Genes like COX5B and MS4A1 emerged as potential predictors of clinical outcomes and therapeutic response. HMGB2 knockdown significantly inhibited cancer cell proliferation, migration, and invasion in female-specific cancers. HMGB2 knockdown in macrophages led to a significant impairment in phagocytosis of breast, cervical, ovarian, and endometrial cancer cells. Furthermore, when HMGB2 knockdown was combined with Palbociclib treatment, a significant decrease in tumor cell proliferation was observed across multiple cancer models.ConclusionThis study highlights the pivotal role of phagocytosis regulators, particularly HMGB2, in the progression of female-specific cancers. Targeting HMGB2 offers promising therapeutic opportunities, potentially enhancing precision oncology and improving patient outcomes.